Grieving Experiences of Parents with Children in End-of-Life Care-A Qualitative Review Protocol - Maria Eduarda Correia; Tânia Melo; Joana Nobre (MDPI AG, 2022)
Parents that accompany their children in end-of-life care until death go through a devastating, complex and vulnerable situation, which is experienced in a unique way and with individual needs, given the specificity of the palliative care setting in which it occurs. This qualitative review aims to identify and synthesize the best evidence available on the grieving experiences of parents with children in end-of-life care in a palliative care setting. This qualitative review protocol is according to the review method proposed by the Joanna Briggs Institute. The results will enable us to identify how parents of children in end-of-life care in a palliative care setting experience their grieving process. This review will broaden the horizon of understanding of the specificities of the grieving experience of parents who have accompanied their children in end-of-life care until their death in a palliative care setting and promote research in this context. The results of the review will also allow the construction of an "end-of-life grieving script", with the aim of identifying one's individuality in the grieving process. This protocol is registered at Open Science Framework.